Innovative Technology System to Prevent Wrong Site Surgery and Capture Near Misses: A Multi-Center Review of 487 Cases - Gloystein, David M.; Heiges, Bradley A.; Schwartz, David G.; DeVine, John G.; Spratt, Deborah (Frontiers in Surgery, 2020)
Introduction: Wrong site surgery (WSS) is a preventable error. When these events do occur, they are often devastating to the patient, nursing staff, surgeon, and facility where the surgery was performed. Despite the implementation of protocols and checklists to reduce the occurrence of WSS, the rates are estimated to be unchanged. Materials and Methods: An innovative technology was designed to prevent WSS through a systems-based approach. The StartBox Patient Safety System was utilized at six sites by eleven surgeons. The incidence of near misses and WSS was reviewed. Results: The StartBox System was utilized for 487 orthopedic procedures including Spine, Sports Medicine, Hand, and Joint Replacement. There were no occurrences of WSS events. Over the course of these procedures, medical staff recorded 17 near misses utilizing the StartBox System. Conclusions: StartBox successfully performed all tasks without technical errors and identified 17 near miss events. The use of this system resulted in the occurrence of zero wrong site surgeries.